2016
DOI: 10.1063/1.4958675
|View full text |Cite
|
Sign up to set email alerts
|

Potential of mean force and transient states in polyelectrolyte pair complexation

Abstract: The association between polyelectrolytes (PEs) of the same size but opposite charge is systematically studied in terms of the potential of mean force (PMF) along their center-of-mass reaction coordinate via coarse-grained, implicit-solvent, explicit-salt computer simulations. The focus is set on the onset and the intermediate, transient stages of complexation. At conditions above the counterion-condensation threshold, the PE association process exhibits a distinct sliding-rod-like behavior where the polymer ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 73 publications
(136 reference statements)
2
22
0
Order By: Relevance
“…29,109 This effect is often invoked during the complexation of two individual polyelectrolytes, 109 and is directly apparent from molecular simulation. [131][132][133][134] Despite the widespread use of this concept to describe complexation of pair complexes, 29,109 only recently has charge localization been regularly invoked in understanding bulk coacervation. 31,97,135…”
Section: Counterion Releasementioning
confidence: 99%
“…29,109 This effect is often invoked during the complexation of two individual polyelectrolytes, 109 and is directly apparent from molecular simulation. [131][132][133][134] Despite the widespread use of this concept to describe complexation of pair complexes, 29,109 only recently has charge localization been regularly invoked in understanding bulk coacervation. 31,97,135…”
Section: Counterion Releasementioning
confidence: 99%
“…Molecular simulations have been applied to probe the interactions among polyelectrolytes [ 26 , 27 , 28 ], including siRNA and synthetic polymers [ 29 ]. Ouyang et al adopted an atomic molecular dynamics simulation to study the complexation of short strand duplex RNA with four cationic carrier systems of varying charge and surface topology at different ratios.…”
Section: Introductionmentioning
confidence: 99%
“…For proteins interacting with the highly charged dPGS macromolecule, it was found that the intrinsic part is dominated by a highly localized electrostatic effect, the counterion-release (CR) contribution: For the highly charged dPGS macromolecule, strong chargerenormalization was observed by a massive uptake of counterions [37]. A few of those counterions "condensed" on the dPGS surface layer are liberated when the protein binds, whereupon an oppositely charged protein patch becomes a multivalent counterion for the polyelectrolyte [58][59][60][61][62][63][64]. The resulting favorable (purely entropic) free energy in dependence of the salt concentration c s can be formulated as:…”
Section: Electrostatic Excess Contributions and Cooperativitymentioning
confidence: 99%